Construction and Structural Analysis of Inter-Regional Industrial Circular Network: A Case of the Middle and Lower Reaches of the Yellow River in China - Chong Yin; Yingxin Cui; Yue Liu; Xiaoni Su (Complexity)
Imbalance, incoordination, and inter-regional economic segmentation of the middle and lower reaches of the Yellow River (MLYR) have brought challenges to high-quality development in the Yellow River basin. To solve the problem, from the perspective of optimization of inter-regional economic circulation, combining input-output technology and complex network model, we proposed a systematic framework for structural analysis of circular economy and applied it in analysis of economic circulation of the MLYR. Firstly, we defined the inter-regional industrial circular network (ICN) and proposed the construction method of the ICN. Secondly, we designed indicators such as network, cycle, and inter-regional circulation effects to measure the structural characteristics of industrial circular network. Thirdly, the models and indicators were applied to explore the structural factors, revealing how the economic circulation was hindered and imbalance of development happened in the MLYR. We found that the external inter-regional circulation of the provinces was more differentiated, and limitation of utilization of technological resources and inter-regional capital flow, and weak investment and consumption demand for emerging services inhabited the quantity and vitality of cycles, which resulted in the imbalance of regional development in the MLYR. The results provide a basis for the suggestion, such as collaborative scientific and technological innovation, building a unified and efficient financial market, and development of emerging industries. The model and method were verified in the case of the MLYR and have practical meaning in supporting policy-making on promoting high-quality development of China.